THE EFFECT OF UREA, KCl, SP-36 FERTILIZER ON PRODUCTION AT SOME AGE OF NATURAL RUBBER PLANT (Hevea brasiliensis Mull.Arg): PENGARUH PUPUK UREA,KCl,SP-36 TERHADAP PRODUKSI PADA BEBERAPA UMUR TANAMAN KARET ALAM (Hevea brasiliensis Mull.Arg) - Gebi Hiskia; Akhmad Sopian; Mahdalena (Universitas Widya Gama Mahakam, 2022)
Gebi Hiskia Anggraini, Faculty of Agriculture, Widya Gama Mahakam University Samarinda 2020,